2012
DOI: 10.1073/pnas.1213622109
|View full text |Cite
|
Sign up to set email alerts
|

Vocal learning is constrained by the statistics of sensorimotor experience

Abstract: The brain uses sensory feedback to correct behavioral errors. Larger errors by definition require greater corrections, and many models of learning assume that larger sensory feedback errors drive larger motor changes. However, an alternative perspective is that larger errors drive learning less effectively because such errors fall outside the range of errors normally experienced and are therefore unlikely to reflect accurate feedback. This is especially crucial in vocal control because auditory feedback can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 27 publications
8
55
0
Order By: Relevance
“…In adults, recent work indicates that the song variability continues to be significant for song plasticity. Trial-by-trial variability in adult song can enable reinforcement learning, and the degree of variability can constrain the amount of plasticity (Tumer and Brainard, 2007;Andalman and Fee, 2009;Charlesworth et al, 2011;Warren et al, 2011;Sober and Brainard, 2012).…”
Section: Trial-and-error: the Role Of Variability In Song Learning Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, recent work indicates that the song variability continues to be significant for song plasticity. Trial-by-trial variability in adult song can enable reinforcement learning, and the degree of variability can constrain the amount of plasticity (Tumer and Brainard, 2007;Andalman and Fee, 2009;Charlesworth et al, 2011;Warren et al, 2011;Sober and Brainard, 2012).…”
Section: Trial-and-error: the Role Of Variability In Song Learning Anmentioning
confidence: 99%
“…Reinforcement models propose the existence of motor ''exploration'' to find actions that result in favorable outcomes and ''exploitation'' to eventually perform just those favorable actions. Moreover, several recent studies have shown that individual differences in the degree of motor variability can predict or constrain the ability to learn or alter motor skills (Sober and Brainard, 2012;Wu et al, 2014). While a handful of studies have described different patterns of basal ganglia activity between behavioral exploration and exploitation states in mammals (Graybiel, 2005;Barnes et al, 2005;Sheth et al, 2011), in many respects, the study of songbirds has been crucial to our current understanding of the nature of trial-by-trial variability, how it is generated in cortical-basal ganglia circuits and its role in behavioral learning and plasticity (Scharff and Nottebohm, 1991;Kao et al, 2005;Ö lveczky et al, 2005;Kao and Brainard, 2006;Tumer and Brainard, 2007;Andalman and Fee, 2009;Mooney, 2009;Stepanek and Doupe, 2010;Fee and Goldberg, 2011;Goldberg and Fee, 2011;Kojima and Doupe, 2011;Warren et al, 2011;Sober and Brainard, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This has significant implications for therapy requirements for users in a clinical or research situation when changing control paradigms. Recent studies suggest that subjects' ability to learn a new paradigm depends on their confidence using the old paradigm: subjects can learn new paradigms more quickly if they are less confident in their old paradigms [28]. It is therefore likely that patients or subjects using one style of device who chose to then begin using both types of device, or a device that allows switching between modes, would need significant occupational therapy training-similar to the training that they received for their initial, single-mode device.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we made the assumptions that there can be cultural mutation between T and t when b T?T and b t?t are not equal to 0 or 1 (Table 1) and that a short or simple repertoire (t) can be more easily learned by a juvenile bird than a long or complex repertoire (T): b t?t [ b T?T . In other words, a juvenile whose father or tutor has a smaller repertoire (t) will only rarely produce a larger repertoire (T), perhaps through copy error, improvisation, or eavesdropping (Beecher et al 2007;Sober and Brainard 2012). However, a juvenile whose father/tutor has a large repertoire (T) might, with a larger probability (1-b T?T [ 1-b t?t ), learn a smaller repertoire (t) than his tutor, perhaps because of the challenges of learning a large repertoire or because he was not exposed to his father's entire repertoire (Botero et al 2008).…”
Section: Methodsmentioning
confidence: 99%